2016
DOI: 10.1038/nm.4038
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 mediates basal and acquired therapy resistance in different subtypes of pancreatic ductal adenocarcinoma

Abstract: Although subtypes of pancreatic ductal adenocarcinoma (PDAC) were described, this malignancy is clinically still treated as a single disease. Here, we present patient-derived models representing the full spectrum of previously identified quasi-mesenchymal (QM-PDA), classical and exocrine-like PDAC subtypes, and identify two markers—HNF1A and KRT81—that enable stratification of tumors into different subtypes by immunohistochemistry. Individuals bearing tumors of these subtypes show significant differences in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
192
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(222 citation statements)
references
References 67 publications
9
192
0
5
Order By: Relevance
“…To date, no correlation has been established between these subtypes and any histological feature, except for the squamous signature that is more frequent in adenosquamous carcinomas. Noll et al [32] proposed that the classification of Collisson et al [29] could be recapitulated by immunochemistry by assessing the expression of HNF1A and KRT81. This requires external validation and no subtype is currently assigned to double-positive tumors, but it may represent an interesting tool to subtype tumors and could have a major clinical impact.…”
Section: Transcriptomic Pdac Subtypesmentioning
confidence: 99%
“…To date, no correlation has been established between these subtypes and any histological feature, except for the squamous signature that is more frequent in adenosquamous carcinomas. Noll et al [32] proposed that the classification of Collisson et al [29] could be recapitulated by immunochemistry by assessing the expression of HNF1A and KRT81. This requires external validation and no subtype is currently assigned to double-positive tumors, but it may represent an interesting tool to subtype tumors and could have a major clinical impact.…”
Section: Transcriptomic Pdac Subtypesmentioning
confidence: 99%
“…The squamous subtype of the disease, which overlaps with the quasi-mesenchymal subtype defined by Collisson and colleagues (21), is characterized by an activated MYC pathway (20) and the poorest outcome (20)(21)(22). These observations moreover reinforce MYC being a relevant driver in PDAC and argue that MYC targeting strategies are needed.…”
mentioning
confidence: 86%
“…37 As part of his presentation, Dr. Trumpp focused on different models for pancreatic ductal adenocarcinoma, including PDX models and primary cell lines derived thereof. He indicated that inhibition of metabolic enzyme cytochrome P450 3A5 (CYP3A5) influences tumor sensitivity to genotoxic drugs and targeted tyrosine kinase inhibitors, 38 thus unveiling CYP3A5 as a new potential target with respect to therapy resistance to clinically used drugs.…”
Section: Tumor Heterogeneitymentioning
confidence: 99%